Female Genital Mutilation and Cutting, an Invisible Pandemic: Examination of The International Legal Framework and Challenges - Pascal Aboh Bekongfe; Linda Nnebuihe Iheanacho; Akpanke Shishitileugiang Aniashie (Universitas Negeri Makassar, 2025)
Female circumcision is a very controversial subject on the African continent and, apparently, across the globe. Whether you are in Kinshasa or Obudu, Nigeria, there seems to be a spectrum of traditional belief systems that justify female circumcision as a panacea to feminine promiscuity, which still suffers the taboo element despite 21st-century development. In this paper, research shows that female circumcision is still rampant. However, the legal framework set up by the international community has a huge role to play in curbing the pandemic. Nevertheless, is the legal framework robust enough to end the threat to womanhood caused by mutilation of the female principal reproductive organ? We opine that more needs to be done, and we utilize real-life experiences from two African communities (the Odo Community of Bayelsa State and the Kassena Nankana region of Northern Ghana) to cement the findings made herein. Our recommendations are straightforward: entrench the legal framework in local communities through the knowledge economy while seriously prosecuting perpetrators of female circumcision, then seal off the opportunities for continuation of these practices by using local chiefs and rulers to enforce compliance. If FGM must end, then myths must be countered with proper sensitization and lies of promiscuity must be countered with evidence to the contrary.